Availability and Distribution of Arsenic in a Corn Crop in the Eastern Zone of the Province of Tucumán, Argentina - Balverdi, María del Pilar; Viruel, Emilce; Ferrero, Marcela; Sales, Adriana María (Fuzzy Publication, India, 2024)
There is a relationship between the arsenic content of crops and that of agricultural soils and the water used for irrigation. The consumption of foods with high arsenical concentrations represents a health risk. Corn is one of the most widely grown cereals in the world due to its ability to adapt to different soils and climates. In northern Argentina, the cultivation of this plant has become more important over the years. However, the groundwater supply of this zone has high arsenic levels. In this study, the levels and distribution of arsenic and its species in soils and corn plants of this agricultural area were determined. Some of the edaphic characteristics that facilitate its phytoavailability were also studied, and the rate of transfer and accumulation of the metalloid in the plant was determined. Elemental determinations were carried out by ICP-MS, FAAS and UV-VisS.